2006
DOI: 10.4049/jimmunol.177.11.8072
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor Induces Macrophage Recruitment via CC Chemokine Ligand 2

Abstract: Macrophage migration inhibitory factor (MIF) was originally identified for its ability to inhibit the random migration of macrophages in vitro. MIF is now recognized as an important mediator in a range of inflammatory disorders. We recently observed that the absence of MIF is associated with a reduction in leukocyte-endothelial cell interactions induced by a range of inflammatory mediators, suggesting that one mechanism whereby MIF acts during inflammatory responses is by promoting leukocyte recruitment. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
159
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(169 citation statements)
references
References 52 publications
7
159
1
2
Order By: Relevance
“…Our studies demonstrate that MIF functions upstream of several inflammatory mediators that have been implicated in the pathogenesis of MS and EAE. Based on our earlier studies, we predict that microglia are the primary source of cytokines/chemokines following intraspinal microinjection of MIF; however, there is evidence that MIF can induce the expression of MCP-1 in microvascular endothelial cells (23). Additionally, a possible direct role for MIF in mediating chemotactic responses cannot be eliminated, as MIF has been shown to recruit both monocytes and T cells via its interaction with CXCR2 and CXCR4, respectively (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies demonstrate that MIF functions upstream of several inflammatory mediators that have been implicated in the pathogenesis of MS and EAE. Based on our earlier studies, we predict that microglia are the primary source of cytokines/chemokines following intraspinal microinjection of MIF; however, there is evidence that MIF can induce the expression of MCP-1 in microvascular endothelial cells (23). Additionally, a possible direct role for MIF in mediating chemotactic responses cannot be eliminated, as MIF has been shown to recruit both monocytes and T cells via its interaction with CXCR2 and CXCR4, respectively (24).…”
Section: Discussionmentioning
confidence: 99%
“…MIF is constitutively expressed, stored intracellularly, and is rapidly released upon encountering activating stimuli. Once secreted, MIF has been shown to exert control over a variety of cellular responses, including cell survival, cytokine production in macrophages, and chemotactic responses (21)(22)(23)(24). Because MIF-induced responses support sustained inflammation, evidence to date points to the detrimental role of MIF in autoimmune and chronic inflammatory disease.…”
Section: Ultiple Sclerosis (Ms) Is a Progressive Immune-mediated Dementioning
confidence: 99%
“…CD68 and CD14 are cell membrane molecule markers for monocytes/macrophages (25,26), highly expressed on activated and mature monocyte/macrophage surface, and CD14 acts as one component of CD14/TLR4/MD2 receptor complex which binds the LPS of gram negative bacteria and facilitates destruction of microbes and induction of various cytokines secretion involved in triggering a wide array of immune responses. We found that activin A significantly increased CD14 and CD68 expression on surface of mouse peritoneal macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MIF impairs p53-dependent apoptosis sustaining activated macrophage lifespan, thus further amplifying the inflammatory response (111) . Another mechanism identified by which MIF promotes inflammation is through amplification of transmigration, recruitment and activation of leukocytes at the site of inflammation through upregulation of adhesion molecules such as intracellular adhesion molecule-1 and chemokine MCP-1 (112)(113)(114) . MIF can exert its chemotactic properties via CXCR2 and CXCR4 in macrophages and T-cells, respectively (114) .…”
Section: Macrophage Migration Inhibitory Factormentioning
confidence: 99%